Niveles de acumulación de plomo por las raíces y tallo de Cortaderia rudiuscula Stapf “cortadera”, en condiciones de laboratorio - Carrera Azañero, Ninjacer (2018)
Environmental pollution is caused by different activities that man develops; however, in recent years more attention has been paid. In Peru, the phytoremediation of natural resources, water and soils in the face of metallic pollutants is an important line of research due to the intense formal and informal mining activity that deteriorates ecosystems; therefore, the objective of the study was to determine the level of lead accumulation in the 0.0 concentrations; 10.0; 20.0; 30.0; 40.0 and 50.0 ppm, for the roots and stem of Cortaderia rudiuscula Stapf "cortadera" under laboratory conditions. The biological material was collected in the district of Agallpampa, Province of Otuzco (La Libertad); the experimental work was carried out in the Environmental Ecotoxicity Laboratory of the National University of Trujillo. The experimental unit was the plant C. rudiuscula Stapf. After a period of adaptation of the plant, the research was carried out in a photo-illumination environment of white light (40W), for ten days. A completely randomized experimental design was applied, with six treatments and three repetitions. The lead solutions were prepared from a 100 ppm standard solution from the lead acetate chemical compound. The concentrations of lead absorbed by the roots and stem of C. rudiuscula Stapf were determined by atomic absorption spectrophotometry. The highest level of lead accumulation was in the root rather than in the stalk of C. rudiuscula Stapf "cortadera". The data were subjected to the Anova tests (α = 0.05) and the Tukey test was performed for the average values of the stem. The highest accumulation of lead was found in the roots of C. rudiuscula Stapf "cortadera", where its maximum average value was 0.809 ppm of lead in the treatment 6 (50ppm) at 240h of evaluation and in the stem its maximum average value was from 0.551 ppm of lead in treatment 6 (50ppm) to 240h of evaluation.